A joint market temporal rolling bidding strategy for virtual power plants in the wholesale market - Mao, Tian; Lin, Hanyang; Cheng, Renli; Li, Jiangnan; Zhou, Baorong; Zhao, Wenmeng; Wang, Tao (Frontiers in Energy Research, 2024)
Massive and diversified distributed energy resources (DERs) have great potential in improving the flexibility of power system operation. However, due to the characteristics of wide distribution, small capacity, and different ownership subjects of DERs, Virtual Power Plants (VPPs) are suitable for aggregating these flexible DERs to participate in the wholesale market. Existing studies focus on how to obtain the bidding strategy in multiple electricity markets. There are shortcomings in the relevant market mechanisms and temporal relationship for participating in energy and ancillary service markets. This paper propose a joint market temporal rolling bidding strategy for VPPs in the wholesale market based on the real market mechanisms of the unified electricity markets in the southern region of China. Based on the proposed method, it can enhance the market-oriented operation profits of VPPs.